Destabilizing Stability? : Exchange Rate Arrangements and Foreign Currency Debt - Csonto, Balazs (IMF Working Papers; Working Paper ;, 2020)
Emerging markets (EMs) often respond to shocks by intervening in foreign exchange (FX) markets and thus preventing full exchange rate adjustment. This response can serve to dampen the effect of shocks and increase monetary policy space but may also incentivize economic participants to increase risk taking and take on more FX debt. This paper empirically analyzes the role of exchange rate flexibility in affecting such risk taking, by using rolling correlations and difference-in-difference estimations. The results suggest that a shift towards greater exchange rate flexibility often coincides with a decline in external FX debt. The findings also highlight the importance of using complementary policies to deal with financial stability issues related to the exchange rate, such as FX-specific macroprudential policies and policies aimed at promoting financial development.